GAMBARAN PENGALAMAN DISKRIMINASI TERHADAP INDIVIDU LGBTQIA+ YANG TERGABUNG DALAM ORGANISASI “S” - Cynthia Eveline Sinulingga; Hadyan Dhiozandi; Ike Meriska; Rininda Mutia; Clara Adjisukmo; Rayini Dahesihsari (Faculty of Psychology, Atma Jaya Catholic University of Indonesia, 2015)
Sexual orientation and sexual identity of the LGBTQIA+(Lesbian, Gay, Bisexual, andTransgender, Questioning, Intersex, Asexual, and others) are some of the common debate topics in the society. Society still consider them as an aberration of moral norms. One of the new-established social organization, organization S, gathers some students to study this topic in a scientific way. The LGBTQIA+ members of organization S, had experienced discrimination from the others because of their sexual preference and sexual identity. The objective of this study is to portray the discrimination that has been experienced by the LGBTQIA+ members in organization S. Researchers used semi-structured interview method for data gathering. Datas are taken from three participants who had experienced discrimination due to their sexual preference and sexual identity. The result will be used as a base of intervention design to reduce discrimination towards LGBTQIA+ members in organization S. Researchers suggest social creativity as the strategy to raise the crowd awareness of the LGBTQIA+ competence and ability as a human, regardless of the negative stigma that they have received before. We suggest a photography exhibition by LGBTQIA+ members of organization S as an intervention programme. The aim of this intervention is to raise awareness of the LGBTQIA+ people, so they will have more positive point of view toward LGBTQIA+ members of this organization. This programme is a part of long term intervention. As a start, researchers suggest a subtler and more acceptable way.